Medication of comorbidities in females with sleep-disordered breathing during long-term CPAP therapy. (August 2020) - Aro, Miia; Saaresranta, Tarja; Vahlberg, Tero; Anttalainen, Ulla
Abstract: Background: Treating sleep disordered breathing (SDB) with nasal continuous positive airway pressure (CPAP) may reduce mortality, but the studies on the effect on medication use are few. Women tend to have more mild sleep apnoea and partial airway obstruction and are therefore expected to have less co-morbidity. The purpose of this study was to evaluate the effect of CPAP therapy on medication use in women as overall medication, and in different subcategories of diseases, and to evaluate the impact of nocturnal airway obstruction type as partial or complete. Methods: From the database of the Department of Pulmonary Diseases in Turku University Hospital from 1994 to 1998, 601 consecutive females with SDB were enrolled, and the type of SDB was evaluated. All were offered CPAP therapy. The medication use measured as defined daily doses (DDD) in overall medication and in nine subcategories were collected three years before and three years after CPAP initiation. Results: In final analyses, 182 women were included. In CPAP users (n = 66), comorbidities were more frequent and DDDs higher overall, in asthma, in chronic obstructive pulmonary disease, and in severe mental disorders, both before and after CPAP initiation. The medication use was similar regardless of the type of SDB. The change in medication use was similar as in controls. Conclusions: CPAP therapy did not decrease medication use in three-year follow-up. However, possibly continuous rise in medication use was prevented, as the change in medication use was similar in controls. Complete and partial obstruction had similar effects. Highlights: Medication use is higher in women using CPAP for SDB compared to the non-users. The difference can be seen three years before and three years after CPAP initiation. Use of asthma, COPD and severe mental illness medication is higher in CPAP users. The medication use was similar in complete and partial obstruction.